COMPLIANCE OF DOCTORS AND MEDICAL ASSISTANTS TO THE NATIONAL PROTOCOL FOR THE TREATMENT OF MALARIA, WAD MEDANI TOWN, GEZIRA STATE - Elhadi A.Yousif, Magda; Abd Elrazig, Sarah A/Monim (مجلة الجزيرة للعلوم الصحية; مجلد 5 عدد 1 (2009), 2009)
Across sectional study to assess the compliance of health workers to the national protocol for the treatment of malaria was conducted in Wad Medani town, (Gezira state) central Sudan. The protocol is a set of recommendations for a unified treatment. The main objectives were to assess the training, knowledge. Attitude and Practices (KAP) of the health providers towards the protocol and to determine different regimens used by them. 126 health workers were interviewed and their prescriptions were reviewed. The study revealed that the vast majority of the health workers (79%) were not trained in the protocol guidelines. Although 93.7% were aware about it, and (90.5%) were adherent to the 1st line of the protocol in the treatment of uncomplicated malaria, only 49.2% were adherent to the 2nd line treatment. In case of severe malaria most of the health workers were found to be not adherent to the protocol guideline 82.2%.The vast majority of the health workers believed that the new antimalarial drugs were effective 84.7% but 79.4% thought that it is costy. Out of the 1471 prescriptions (22.1%) were for antimalarial treatment the majority of them were written by Medical Officers. The most common antimalarial used was artemether (51.1%). Regarding the parentral artemether 14.2% was prescribed in smaller dose. However about 81.2% of antimalarial drugs prescription for simple malaria was judged to be adquate and conforming with the protocol.